Patterns of cardiovascular risk in rheumatoid arthritis. Issue 12 (22nd June 2006) - Solomon, D H; Goodson, N J; Katz, J N; Weinblatt, M E; Avorn, J; Setoguchi, S; Canning, C; Schneeweiss, S
Abstract : Background: Although it is known that rheumatoid arthritis is associated with an increased risk of cardiovascular disease (CVD), the pattern of this risk is not clear. This study investigated the relative risk of myocardial infarction, stroke and CVD mortality in adults with rheumatoid arthritis compared with adults without rheumatoid arthritis across age groups, sex and prior CVD event status. Methods: We conducted a cohort study among all residents aged ⩾18 years residing in British Columbia between 1999 and 2003. Residents who had visited the doctor at least thrice for rheumatoid arthritis (International Classification of Disease = 714) were considered to have rheumatoid arthritis. A non-rheumatoid arthritis cohort was matched to the rheumatoid arthritis cohort by age, sex and start of follow-up. The primary composite end point was a hospital admission for myocardial infarction, stroke or CVD mortality. Results: 25 385 adults who had at least three diagnoses for rheumatoid arthritis during the study period were identified. During the 5-year study period, 375 patients with rheumatoid arthritis had a hospital admission for myocardial infarction, 363 had a hospitalisation for stroke, 437 died from cardiovascular causes and 1042 had one of these outcomes. The rate ratio for a CVD event in patients with rheumatoid arthritis was 1.6 (95% confidence interval (CI) 1.5 to 1.7), and the rate difference was 5.7 (95% CI 4.9 to 6.4) per 1000 person-years. The rate ratio decreased with age, from 3.3 in patients aged 18–39 years to 1.6 in those aged ⩾75 years. However, the rate difference was 1.2 per 1000 person-years in the youngest age group and increased to 19.7 per 1000 person-years in those aged ⩾75 years. Among patients with a prior CVD event, the rate ratios and rate differences were not increased in rheumatoid arthritis. Conclusions: This study confirms that rheumatoid arthritis is a risk factor for CVD events and shows that the rate ratio for CVD events among subjects with rheumatoid arthritis is highest in young adults and those without known prior CVD events. However, in absolute terms, the difference in event rates is highest in older adults.